New financial spaces drawn by institutional regulatory barriers. What effects on territorial sustainable development? - Varraso, Isabella; Cesari, Oriana (European Journal of Sustainable Development, 2016)
Financial flows affect sustainability. Financial regulation has a central role in sustainable development of regions. Recent crisis of 2008 has shown how financial space equilibrium is entangled with economic stability of territories so that changes in financial space can transform local and global financial conditions. Considering the need to develop sustainable relations between financial space and real economy, the aim of this article is to examine, from a geographical perspective, how international institutions may create or reduce, through regulatory mechanism, barriers to the effects of uncontrolled financial flows. Reproducing spaces involved and drawing results using cartography, poles and barriers are considered. As result, a space is outlined where is possible to study future diffusion patterns and consider if the barrier system observed reveals to be absorbing in the sense that financial contagion prevention is achieved with a significant reduction of risk, or if it is not absorbing so that risk shifts to lower levels of geographical scale reaching for the intersections between financial space and everyday economic life of territories involved. Key Words: Financial space, Financial flows, Financial Geography, International Institutions, Regulatory barriers